2015
DOI: 10.1111/nph.13463
|View full text |Cite
|
Sign up to set email alerts
|

Central role of FaGAMYB in the transition of the strawberry receptacle from development to ripening

Abstract: SummaryThe receptacle of the strawberry (Fragaria 9 ananassa) fruit accounts for the main properties of the ripe fruit for human consumption. As it ripens, it undergoes changes similar to other fruits in sugar : acid ratio, volatile production and cell wall softening. However, the main regulators of this process have not yet been reported. The white stage marks the initiation of the ripening process, and we had previously reported a peak of expression for a FaGAMYB gene.Transient silencing of FaGAMYB using RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 58 publications
2
56
0
Order By: Relevance
“…Here, we found that silencing of FaMADS9 causes changes in the expression of an elevated number of ARFs but also a drastic reduction in the expression of ABA‐synthesizing genes such as FaNCED1 , FaNCED2 and FaNCED3 in the transgenic receptacles, and a subsequent decrease in AB A content. Silencing of FaNCED1 and FaNCED2 was observed in FaGAMYB ‐silenced receptacles (Vallarino et al , ), as well as reduced levels of ABA in the transgenic tissue. Notably, the ASR gene ( FvH4_2g13410 ), which is involved in the ABA transduction pathway, was up‐regulated in red receptacles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we found that silencing of FaMADS9 causes changes in the expression of an elevated number of ARFs but also a drastic reduction in the expression of ABA‐synthesizing genes such as FaNCED1 , FaNCED2 and FaNCED3 in the transgenic receptacles, and a subsequent decrease in AB A content. Silencing of FaNCED1 and FaNCED2 was observed in FaGAMYB ‐silenced receptacles (Vallarino et al , ), as well as reduced levels of ABA in the transgenic tissue. Notably, the ASR gene ( FvH4_2g13410 ), which is involved in the ABA transduction pathway, was up‐regulated in red receptacles.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the hormones have been reported to participate in strawberry fruit development and ripening (Chai et al , ; Csukasi et al , ; Estrada‐Johnson et al , ; Jia et al , ; Merchante et al , ; Mezzetti et al , ), and they are expected to play a main role in the regulation of the process. However, the interplay between hormones and regulatory genes has scarcely been addressed (Csukasi et al , ; Vallarino et al , ). Here, we found that silencing of FaMADS9 causes changes in the expression of an elevated number of ARFs but also a drastic reduction in the expression of ABA‐synthesizing genes such as FaNCED1 , FaNCED2 and FaNCED3 in the transgenic receptacles, and a subsequent decrease in AB A content.…”
Section: Discussionmentioning
confidence: 99%
“…The bHLH proteins have not been extensively studied in plants. Those that have been characterized function in anthocyanin biosynthesis, phytochrome signaling, globulin expression, fruit dehiscence, and carpel and epidermal development5253. Consequently, gene27422 could encode a bHLH TF regulating pigment formation in strawberry fruit.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we were able to apply the protocol for the extraction, detection and identification of primary and/or secondary metabolites of several species and tissues. Amongst others, we studied Arabidopsis thaliana seedlings [32], roots and leaves [23], barley ( Hordeum vulgare ) [62], wild strawberry ( Fragaria vesca ) [63] strawberry ( Fragaria X ananassa ) [64], the root tissue of maize ( Zea mays ) [65], the green algae Chlamydomonas reinhardtii [66], the marine diatom Thalassiosira pseudonana [61] and some low phosphate-tolerant proteaceae species [51]. …”
Section: Discussionmentioning
confidence: 99%